Pengaruh Kepemimpinan, Budaya Kerja dan Motivasi Kerja Terhadap Kinerja Perangkat Nagari Melalui Organizational Citizenship Behavior Sebagai Variabel Intervening pada Nagari di Kecamatan X Koto Diatas Kabupaten Solok - Herlina, Herlina; Elfiswandi, Elfiswandi; Veri, Jhon (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the influence of leadership, work culture, and work motivation on the performance of village officials with Organizational Citizenship Behavior (OCB) as an intervening variable in X Koto Diatas Subdistrict, Solok Regency. The study used a quantitative method with SEM-PLS analysis and involved 100 village officials as respondents. The results showed that leadership and work culture had a positive but insignificant effect on OCB, while work motivation had a positive and significant effect. Leadership has a positive but insignificant effect on performance, while work culture and work motivation have a positive and significant effect. OCB is proven not to mediate the effect of leadership and work culture on performance, but is able to mediate the effect of work motivation. In addition, OCB has a positive and significant effect on performance. These findings confirm that work motivation has the most dominant effect in improving the performance of nagari officials.